Prevalence and risk of thyroid disease among adult primary aldosteronism patients: a systematic review, meta-analysis, and trial sequential analysis - Hu, Wansong; Wu, Yingxing; Li, Ping (Frontiers in Endocrinology, 2025)
BackgroundPrimary aldosteronism (PA), the most prevalent curable secondary hypertension, and thyroid diseases (the second most common endocrine disorder) are increasingly linked, yet their mechanistic connections remain unclear.Design and methodsFour databases (PubMed, Embase, Web of Science, Cochrane Library) were searched for case-control studies. Random-effects meta-analysis and subgroup analyses for thyroid disease subtypes were performed. Sensitivity/trial sequential analyses and Begg’s test evaluated robustness/publication bias.ResultsOur meta-analysis included five case-control studies, encompassing 1,368 patients with primary aldosteronism (PA) and 6,774 controls. While the overall prevalence of thyroid diseases was higher in PA patients (OR: 1.33, 95% CI: 1.03-1.71, p=0.03), subgroup analysis revealed that this association was primarily driven by a significantly increased prevalence of thyroid nodules (OR: 1.85, 95% CI: 1.23-2.80, p=0.003). No statistically significant associations were found between PA and other specific thyroid conditions, including hyperthyroidism, hypothyroidism, thyroiditis, or thyroid cancer (all p > 0.05).ConclusionsThis first meta-analysis demonstrates a significant PA-thyroid disease association. The elevated overall risk of thyroid disease in PA patients appears to be largely attributable to the high burden of thyroid nodules. These findings suggest that patients with PA may benefit from targeted screening for thyroid nodules.